Overexpression of a Sugarcane BAHD Acyltransferase Alters Hydroxycinnamate Content in Maize Cell Wall - Fanelli, Amanda; Rancour, David M.; Sullivan, Michael; Karlen, Steven D.; Ralph, John; Riaño-Pachón, Diego Mauricio; Vicentini, Renato; Silva, Tatiane da Franca; Ferraz, André; Hatfield, Ronald D.; Romanel, Elisson (Frontiers in Plant Science, 2021)
The purification of hydroxycinnamic acids [p-coumaric acid (pCA) and ferulic acid (FA)] from grass cell walls requires high-cost processes. Feedstocks with increased levels of one hydroxycinnamate in preference to the other are therefore highly desirable. We identified and conducted expression analysis for nine BAHD acyltransferase ScAts genes from sugarcane. The high conservation of AT10 proteins, together with their similar gene expression patterns, supported a similar role in distinct grasses. Overexpression of ScAT10 in maize resulted in up to 75% increase in total pCA content. Mild hydrolysis and derivatization followed by reductive cleavage (DFRC) analysis showed that pCA increase was restricted to the hemicellulosic portion of the cell wall. Furthermore, total FA content was reduced up to 88%, resulting in a 10-fold increase in the pCA/FA ratio. Thus, we functionally characterized a sugarcane gene involved in pCA content on hemicelluloses and generated a C4 plant that is promising for valorizing pCA production in biorefineries.